Triphenylamine-based conjugated microporous polymer as well as preparation method and application thereof
By using triphenylamine-based conjugated microporous polymers as photocatalysts, the problems of easy oxidation, instability and low activity of photocatalysts in the existing technology are solved, and efficient photocatalytic water splitting to produce hydrogen is achieved, with high hydrogen evolution efficiency. speed and good stability.
Patent Information
- Application Number
- CN202411456844.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The photocatalysts used in the prior art for hydrogen production have problems such as oxidation, instability and low activity, which limit their large-scale application.
Using triphenylamine-based conjugated microporous polymer as a photocatalyst, the material was synthesized through Sonogashira coupling reaction, and its purity was improved through extraction and purification steps.
It achieves a high hydrogen evolution rate (8-27mmol/h/g) in the process of photocatalytic water splitting to produce hydrogen, and has good chemical stability and thermal stability.
Smart Images

Figure CN119331227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a photocatalyst, in particular to a triphenylamine-based conjugated microporous polymer and a preparation method and application thereof. Background Art
[0002] Energy is the basic material basis for human survival and an important guarantee for the sustainable development of social economy. Since the 20th century, the rapid progress of science and technology and the sustained development of economy have brought about significant changes in life, but at the same time, problems such as resource shortage, environmental pollution and ecological imbalance have become increasingly serious, especially environmental pollution and energy depletion have become two major challenges for human development. In order to cope with these problems, it is crucial to accelerate the development of clean energy. The development and utilization of renewable clean energy has been widely recognized around the world. In this context, the development of new clean and renewable energy is particularly important. Solar energy has been promoted to study photocatalytic water hydrogen production catalysts due to its inexhaustible characteristics and the advantages of hydrogen energy such as clean and pollution-free and high combustion value. By irradiating sunlight on the catalyst, triggering the transition of photons, decomposing water to produce hydrogen under specific conditions, the conversion of solar energy into chemical energy is realized. As a clean secondary energy source, hydrogen has broad application prospects, and the photocatalytic water decomposition hydrogen production technology is more in line with the requirements of green environmental protection than traditional hydrogen production methods, and is known as the most ideal hydrogen production technology.
[0003] In the prior art, photocatalysts used for hydrogen production are mainly metal-containing inorganic semiconductors, which face problems such as easy oxidation, instability, low activity, and limited metal resources. From the perspective of sustainable development, pure organic semiconductor photocatalysts are particularly important in the field of photocatalytic water decomposition to produce hydrogen, especially conjugated microporous polymers, which have attracted extensive attention from researchers due to their rich raw material sources, simple synthesis methods, and easily regulated structures.
[0004] At present, the rate of hydrogen production by organic conjugated polymers as photocatalysts is not high and cannot be compared with metal-containing inorganic semiconductor catalysts, which limits their large-scale application. For example, the invention patent with publication number CN111804338A discloses a triazine-based DA-type nitrogen-containing organic conjugated porous polymer photocatalytic material, which is made by combining tripolyazine and DA-type pyrazole small molecules. Although the material has good dispersibility and stability, its maximum hydrogen production rate (HER) is only 1000 μmol / h / g. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a triphenylamine-based conjugated microporous polymer having a high hydrogen evolution rate in the process of photocatalytic water decomposition to produce hydrogen, and having good chemical stability and thermal stability, as well as a preparation method and application thereof.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A triphenylamine-based conjugated microporous polymer, the structure of which is shown in the following formula (I):
[0008]
[0009] In formula (I), represents one of the following formulas (A1), (A2), (A3) and (A4):
[0010]
[0011] In the above formulae, * represents a connecting bond position.
[0012] The preparation method of the triphenylamine-based conjugated microporous polymer comprises: placing a functional ligand, an auxiliary monomer, an organic solvent and a weak base in a reaction container, adding a palladium catalyst and a monovalent copper catalyst, heating and reacting under an atmosphere protection condition, filtering, collecting solids, and obtaining a crude target product; wherein,
[0013] The functional ligand is tri(4-ethynylphenyl)amine; the auxiliary monomer is one selected from 2,7-dibromopyrene, 1,4-dibromonaphthalene, 4,4-dibromobiphenyl and 1,4-dibromobenzene.
[0014] The present invention adopts Sonogashira coupling reaction, places functional ligand and auxiliary monomer in organic solvent, weak base provides alkalinity for the system, and performs coupling reaction in the presence of palladium catalyst and monovalent copper catalyst under protective atmosphere to synthesize the triphenylamine-based conjugated microporous polymer.
[0015] In the above preparation method, the dosage of the functional ligand and the auxiliary monomer is a stoichiometric ratio. The organic solvent is preferably N, N-dimethylformamide, N, N-dimethylacetamide, toluene or tetrahydrofuran; its dosage is calculated based on 1mmol of the functional ligand, and 60-90mL of organic solvent is preferably used for all the raw materials participating in the reaction. The weak base is preferably a combination of one or two of triethylamine, diethylamine, sodium carbonate, potassium carbonate or cesium carbonate, and the dosage of the weak base is preferably 2-4 times the molar amount of the functional ligand. For palladium catalysts and monovalent copper catalysts, their selection and dosage are conventional choices in the prior art, wherein the palladium catalyst is preferably tetrakis(triphenylphosphine)palladium and / or bistriphenylphosphine palladium dichloride, and its dosage is preferably 0.05-0.07 times the molar amount of the functional ligand. For monovalent copper catalysts, monovalent copper halides such as cuprous iodide, cuprous chloride or cuprous bromide are usually selected, and its dosage is preferably 0.2-0.3 times the molar amount of the functional ligand.
[0016] In the above preparation method, the reaction is preferably carried out at ≥90°C, and more preferably at 95-120°C; when the reaction is carried out at 95-120°C, the reaction time is preferably controlled at 72-96h.
[0017] The crude product of the target product is prepared by the above method. When it is used, the purity of the product needs to be improved. Therefore, the method of the present invention also includes the step of purifying the crude product of the target product obtained, specifically: extracting the crude product of the target product with an extractant, or washing the crude product of the target product with an extractant and then extracting it, collecting the solid phase, and obtaining the target product. The extractant involved in the purification method can be dichloromethane, or a combination of dichloromethane and one or more of toluene, acetone and methanol. When performing the extraction, it is preferred to use the Soxhlet extraction method, and the extractant used is preferably a composition of dichloromethane, methanol and toluene in a volume ratio of 1.5-2:0.8-1.0:0.8-1.0. The purification step is preferably washing first and then extracting.
[0018] The purified triphenylamine-based conjugated microporous polymer needs to be conventionally activated before being used for photocatalytic hydrolysis to produce hydrogen, such as soaking the triphenylamine-based conjugated microporous polymer in n-hexane (the soaking time is usually ≥24h), then filtering, and then drying the obtained solid.
[0019] The applicant has found in experiments that the triphenylamine-based conjugated microporous polymer has high photocatalytic activity when used as a photocatalyst to produce hydrogen by hydrolysis, and can be used as a photocatalyst. Therefore, the present invention also includes the use of the triphenylamine-based conjugated microporous polymer in photocatalytic hydrogen production.
[0020] Compared with the prior art, the present invention provides a novel triphenylamine-based conjugated microporous polymer and its preparation method and application. The applicant's test results show that the triphenylamine-based conjugated microporous polymer used as a catalyst in the process of photocatalytic water decomposition to produce hydrogen exhibits excellent catalytic activity (hydrogen evolution rate of 8 to 27 mmol / h / g), and has good chemical stability and thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Fourier transform infrared spectra (FT-IR) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0022] Figure 2 The solid state nuclear magnetic resonance carbon spectrum of the conjugated microporous polymer TA-DPE prepared in Example 1 of the present application ( 13 C-SSNMR);
[0023] Figure 3X-ray photoelectron spectroscopy (XPS) of the conjugated microporous polymer TA-DPE prepared in Example 1 of the present application;
[0024] Figure 4 X-ray powder diffraction spectra (PXRD) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0025] Figure 5 Scanning electron microscope images (SEM) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0026] Figure 6 The specific surface area detection spectra (BET) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0027] Figure 7 Thermogravimetric analysis spectra (TGA) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0028] Figure 8 Fourier transform infrared spectra (FT-IR) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0029] Fig. 9 Ultraviolet-visible diffuse reflectance spectra (UV-Vis) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0030] Fig.10 The variable temperature fluorescence spectra (variable temperature PL) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0031] Fig.11 Electrochemical impedance spectroscopy (EIS) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0032] Fig.12 The photocurrent response curve spectra (i-t curves) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application;
[0033] Fig.13Time-resolved photoluminescence spectra (TRPL) of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application.
[0034] Fig.14 This is a bar graph of the hydrogen evolution rates of the conjugated microporous polymers TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 of the present application as photocatalysts in the water decomposition hydrogen production experiment. DETAILED DESCRIPTION
[0035] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.
[0036] Example 1
[0037]
[0038] 1) Add tri(4-ethynylphenyl)amine (1.000mmol, 0.317g) and 2,7-dibromopyrene (1.500mmol, 0.540g) to a 250mL round-bottom flask, then add tetrakis(triphenylphosphine)palladium (0.061mmol, 0.070g) and cuprous iodide (0.263mmol, 0.050g), then add 80mL N,N-dimethylformamide (DMF) and 40mL triethylamine, under nitrogen atmosphere, react in an oil bath at 105°C for 72h, cool to room temperature after the reaction, and filter under reduced pressure to obtain a crude product.
[0039] 2) The crude product was washed three times with 200 mL of dichloromethane, placed in an extraction bottle of a 150 mL Soxhlet extraction apparatus, and then an extractant (consisting of 30 mL of dichloromethane, 15 mL of methanol and 15 mL of toluene) was added. The extraction bottle was placed in an oil bath at 130° C. and condensed and refluxed for 24 h to remove impurities to obtain 0.56 g of the purified target product, which was recorded as TA-DPE.
[0040] Example 2
[0041]
[0042] 1) Add tri(4-ethynylphenyl)amine (1.000mmol, 0.317g) and 1,4-dibromonaphthalene (1.500mmol, 0.429g) to a 250mL round-bottom flask, then add tetrakis(triphenylphosphine)palladium (0.061mmol, 0.070g) and cuprous iodide (0.263mmol, 0.050g), then add 80mL N,N-dimethylformamide (DMF) and 40mL triethylamine, under nitrogen atmosphere, react in an oil bath at 105°C for 72h, cool to room temperature after the reaction, and filter under reduced pressure to obtain a crude product.
[0043] 2) The crude product was washed three times with 200 mL of dichloromethane in sequence, placed in an extraction bottle of a 150 mL Soxhlet extraction apparatus, and then an extractant (consisting of 30 mL of dichloromethane, 15 mL of methanol and 15 mL of toluene) was added. The extraction bottle was placed in an oil bath at 130° C. and condensed and refluxed for 24 h to remove impurities, and 0.51 g of the purified target product was obtained. The obtained product was recorded as TA-DNP.
[0044] Example 3
[0045]
[0046] 1) Tri(4-ethynylphenyl)amine (1.000mmol, 0.317g) and 4,4-dibromobiphenyl (1.500mmol, 0.468g) were added to a 250mL round-bottom flask, and then tetrakis(triphenylphosphine)palladium (0.061mmol, 0.070g) and cuprous iodide (0.263mmol, 0.050g) were added, and then 80mL N,N-dimethylformamide (DMF) and 40mL triethylamine were added. The mixture was reacted in an oil bath at 105°C under a nitrogen atmosphere for 72h. After the reaction was completed, the mixture was cooled to room temperature and filtered under reduced pressure to obtain a crude product.
[0047] 2) The crude product was washed three times with 200 mL of dichloromethane, then placed in an extraction bottle of a 150 mL Soxhlet extraction apparatus, and an extractant (consisting of 30 mL of dichloromethane, 15 mL of methanol and 15 mL of toluene) was added, and the extraction bottle was placed in an oil bath at 130° C. and condensed and refluxed for 24 h to remove impurities, to obtain 0.49 g of the purified target product, which was recorded as TA-DBS.
[0048] Example 4
[0049]
[0050] 1) Tri(4-ethynylphenyl)amine (1.000mmol, 0.317g) and 1,4-dibromobenzene (1.500mmol, 0.354g) were added to a 250mL round-bottom flask, and then tetrakis(triphenylphosphine)palladium (0.061mmol, 0.070g) and cuprous iodide (0.263mmol, 0.050g) were added, and then 80mL N,N-dimethylformamide (DMF) and 40mL triethylamine were added. The mixture was reacted in an oil bath at 105°C under a nitrogen atmosphere for 72h. After the reaction was completed, the mixture was cooled to room temperature and filtered under reduced pressure to obtain a crude product.
[0051] 2) The crude product was washed three times with 200 mL of dichloromethane, and then placed in an extraction bottle of a 150 mL Soxhlet extraction apparatus, and an extractant (consisting of 30 mL of dichloromethane, 15 mL of methanol and 15 mL of toluene) was added, and the extraction bottle was placed in an oil bath at 130° C. and condensed and refluxed for 24 h to remove impurities, to obtain 0.47 g of the purified target product, which was recorded as TA-DB.
[0052] The target products prepared in Examples 1, 2, 3 and 4 above were characterized and analyzed, and the results were as follows:
[0053] 1. Fourier transform infrared spectroscopy analysis
[0054] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1 to 4 were characterized and analyzed by Fourier transform infrared spectroscopy (FT-IR). The characterization results are as follows: Figure 1 shown.
[0055] Depend on Figure 1 It can be seen that the strong absorption band of TA observed at 3263cm-1 is related to its ≡CH stretching vibration, while a new C≡C signal appears in TA-DPE, TA-DNP, TA-DBS and TA-DB at 2200cm-1. These signals confirm the structural characteristics and indicate that the monomers are successfully coupled to the polymers. In addition, the stretching vibration bands of the aromatic C=C and CN of the triphenylamine part are located at 1590cm-1 and 1320cm-1, respectively, which preliminarily indicates the successful synthesis of the polymer.
[0056] 2. Solid-state carbon nuclear magnetic resonance spectroscopy analysis
[0057] Solid-state carbon nuclear magnetic resonance spectroscopy ( 13 C-SSNMR) was used to characterize the TA-DPE obtained in Example 1. The characterization results are as follows: Figure 2 shown.
[0058] Depend on Figure 2It can be seen that a unique characteristic peak is observed at -20 to -30 ppm for TA-DPE, which clearly indicates the presence of alkyne groups in the triphenylamine-based conjugated microporous polymer, confirming the successful synthesis of TA-DPE.
[0059] 3. X-ray photoelectron spectroscopy analysis
[0060] The TA-DPE prepared in Example 1 was characterized and analyzed by X-ray photoelectron spectroscopy (XPS). Figure 3 shown.
[0061] Depend on Figure 3 It can be seen that the Br content in the TA-DPE unit is almost undetectable, which confirms the successful completion of the reaction.
[0062] 4. X-ray powder diffraction spectrum analysis
[0063] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized by X-ray powder diffraction (PXRD). Figure 4 shown.
[0064] Figure 4 The characteristic broad peaks are shown, indicating that TA-DPE, TA-DNP, TA-DBS and TA-DB materials are all amorphous structures.
[0065] 5. Scanning Electron Microscope Image Analysis
[0066] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by scanning electron microscopy (SEM). Figure 5 shown.
[0067] Depend on Figure 5 It can be seen that the morphology of TA-DPE is different from that of TA-DNP, TA-DBS and TA-DB. TA-DPE presents a network morphology, while TA-DNP, TA-DBS and TA-DB present a spherical morphology. This special morphology helps to expose more active sites, thereby increasing the catalytic efficiency.
[0068] 6.BET test characterization spectrum analysis
[0069] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by the specific surface area detection method (BET). The characterization results are as follows: Figure 6 shown.
[0070] Depend on Figure 6It can be seen that the pore size of TA-DNP is 1.190nm, while the pore size of TA-DPE, TA-DBS and TA-DB is 1.045nm, which confirms the microporous characteristics of CMP. In addition, the BET specific surface area analysis results of TA-DPE, TA-DNP, TA-DBS and TA-DB show that their specific surface areas are 662.49, 651.09, 418.33 and 371.67m, respectively. 2 / g. A higher specific surface area is beneficial to increasing the contact area, thereby increasing the reaction rate.
[0071] 7. Thermal stability analysis
[0072] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized by thermogravimetric analysis (TGA). Figure 7 shown.
[0073] Depend on Figure 7 It can be seen that TA-DPE, TA-DNP, TA-DBS and TA-DB begin to lose weight after 300°C, proving that the triphenylamine conjugated microporous polymer has good thermal stability.
[0074] 8. Chemical stability analysis
[0075] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by Fourier transform infrared spectroscopy (FT-IR). Figure 8 shown.
[0076] Depend on Figure 8 It can be seen that the structures of TA-DPE, TA-DNP, TA-DBS and TA-DB did not change after being immersed in dichloromethane (CH2Cl2), N,N-dimethylformamide (DMF), water (H2O), 6mol / L HCl solution and 6mol / LNaOH solution for 3 days, respectively, which proves that these materials have high chemical resistance to acidic, alkaline and humid environments.
[0077] 9. UV-Vis diffuse reflectance spectroscopy analysis
[0078] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by UV-Vis diffuse reflectance spectroscopy. The characterization results are shown in FIG. Fig. 9 shown.
[0079] Depend on Fig. 9It can be seen that TA-DPE, TA-DNP, TA-DBS and TA-DB have a wide range of light absorption, which proves their good light harvesting ability. According to the Kubelka-Munk equation αhν=A(ν-Eg) n / 2 (where α, h, ν, A and Eg represent the absorption coefficient, Planck constant, light frequency, constant and semiconductor bandgap width, respectively). The calculation shows that their band gaps are 2.07, 2.12, 2.16 and 2.22 eV, respectively.
[0080] 10. Temperature-dependent fluorescence spectroscopy
[0081] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by using variable temperature fluorescence spectroscopy. The characterization results are shown in FIG. Fig.10 shown.
[0082] Depend on Fig.10 It can be seen that the exciton binding energies of TA-DPE, TA-DNP, TA-DBS and TA-DB are 75.5, 85.8, 90.7 and 99.6 meV respectively. The lower the exciton binding energy, the lower the energy required for the separation of electron-hole pairs (i.e., excitons), which is conducive to the effective separation of electrons and holes, thereby improving the photoelectric conversion efficiency.
[0083] 11. Electrochemical impedance spectroscopy
[0084] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by electrochemical impedance spectroscopy (EIS). Fig.11 shown.
[0085] Depend on Fig.11 It can be seen that TA-DPE has the smallest impedance and TA-DB has the largest impedance.
[0086] 12. Photocurrent response curve analysis
[0087] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized and analyzed by using the photocurrent response curve test (i-t curve). The characterization results are as follows: Fig.12 shown.
[0088] Depend on Fig.12 It can be seen that TA-DPE, TA-DNP, TA-DBS and TA-DB can all separate electrons and holes.
[0089] 13. Time-resolved photoluminescence spectroscopy
[0090] The TA-DPE, TA-DNP, TA-DBS and TA-DB prepared in Examples 1, 2, 3 and 4 were characterized by time-resolved photoluminescence (TRPL) spectroscopy. Fig.13 shown.
[0091] Depend on Fig.13 It can be seen that the fluorescence lifetimes of TA-DPE, TA-DNP, TA-DBS and TA-DB are 20.4, 18.2, 15.3 and 11.8 ns, respectively. The longer fluorescence lifetime leads to higher charge mobility, which can provide more free photogenerated charges to participate in surface reactions, thereby improving the photocatalytic efficiency.
[0092] Example 5
[0093] Example 1 was repeated, except that tetrahydrofuran was used instead of N,N-dimethylformamide, bistriphenylphosphine palladium dichloride was used instead of tetrakis(triphenylphosphine)palladium, cuprous chloride was used instead of cuprous iodide, and sodium carbonate was used instead of triethylamine.
[0094] The product obtained in this example was analyzed by Fourier infrared spectroscopy, carbon nuclear magnetic resonance spectroscopy and X-ray photoelectron spectroscopy, and was determined to be the target product TA-DPE.
[0095] Example 6
[0096] Example 2 was repeated, except that toluene was used instead of N,N-dimethylformamide, cesium carbonate was used instead of triethylamine, the reaction was carried out at 90° C., and the reaction time was changed to 96 h.
[0097] The product obtained in this example was analyzed by Fourier infrared spectroscopy and X-ray photoelectron spectroscopy, and was determined to be the target product TA-DNP.
[0098] Example 7
[0099] Example 3 was repeated, except that N,N-dimethylacetamide was used instead of N,N-dimethylformamide, potassium carbonate was used instead of triethylamine, cuprous chloride was used instead of cuprous iodide, and the reaction was carried out at 115°C.
[0100] The product obtained in this example was analyzed by Fourier infrared spectroscopy and X-ray photoelectron spectroscopy, and was determined to be the target product TA-DBS.
[0101] Application Examples
[0102] In order to investigate the effect of the triphenylamine-based conjugated microporous polymer of the present invention as a photocatalyst in producing hydrogen by decomposing water, the following method was used to test its photocatalytic performance.
[0103] The experiment was carried out in an analytical test system. Before the reaction started, the air in the system was removed by nitrogen bubbling, and a 300W xenon lamp was used as the light source.
[0104] The experimental process of photocatalytic hydrogen production is as follows: weigh 0.5 mg of triphenylamine-based conjugated microporous polymer on a one-hundred-thousandth balance and add it to a 25 mL quartz tube; then weigh 20 mg of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole (BIH) and add it to the quartz tube. Next, use a pipette to take 3 mL of acetonitrile, 1.5 mL of triethylamine and 1 mL of water and add them to the quartz tube. Seal the quartz tube, ultrasonically treat it for 10 minutes, bubble it with nitrogen for 20 minutes, then irradiate it with a 300W xenon lamp and stir it, and react it at room temperature for 2 hours. After the reaction is completed, use an Agilent 8860 gas chromatograph for detection and analysis, and the test results are shown in Table 1. The hydrogen evolution rate data in Table 1 are organized into a bar graph, as shown in Fig.14 shown.
[0105] Table 1 Hydrogen evolution rate of triphenylamine-based conjugated microporous polymer photocatalyst (mmol / g / h)
[0106] TA-DPE TA-DNP TA-DBS TA-DB Hydrogen evolution rate 27 23 12 8
[0107] The above experiments show that the triphenylamine-based conjugated microporous polymer of the present invention has a high hydrogen evolution rate and can achieve efficient photocatalytic water decomposition to produce hydrogen.
Claims
1. A triphenylamine-based conjugated microporous polymer, the structure of which is shown in the following formula (I): In formula (I), represents one of the following formulas (A1), (A2), (A3) and (A4): In the above formulae, * represents a connecting bond position.
2. The method for preparing the triphenylamine-based conjugated microporous polymer according to claim 1, characterized in that: The functional ligand, auxiliary monomer, organic solvent and weak base are placed in a reaction container, palladium catalyst and monovalent copper catalyst are added, heating reaction is carried out under atmosphere protection conditions, and solids are collected by filtering to obtain a crude target product; wherein, The functional ligand is tri(4-ethynylphenyl)amine; the auxiliary monomer is one selected from 2,7-dibromopyrene, 1,4-dibromonaphthalene, 4,4-dibromobiphenyl and 1,4-dibromobenzene.
3. The preparation method according to claim 2, characterized in that: The organic solvent is N, N-dimethylformamide, N, N-dimethylacetamide, toluene or tetrahydrofuran.
4. The preparation method according to claim 2, characterized in that: The weak base is one or a combination of two of triethylamine, diethylamine, sodium carbonate, potassium carbonate or cesium carbonate.
5. The preparation method according to claim 2, characterized in that: The monovalent copper catalyst is a monovalent copper halide.
6. The preparation method according to claim 2, characterized in that: The reaction was carried out at ≥90°C.
7. The preparation method according to any one of claims 2 to 6, characterized in that: The method also includes a step of purifying the obtained crude target product.
8. The preparation method according to claim 7, characterized in that: The step of purifying the crude target product is: extracting the crude target product with an extractant, or first washing the crude target product with an extractant and then extracting it, collecting the solid phase, and obtaining the target product.
9. The preparation method according to claim 8, characterized in that: The extractant is dichloromethane, or a combination of dichloromethane and one or more of toluene, acetone and methanol.
10. Use of the triphenylamine-based conjugated microporous polymer according to claim 1 in photocatalytic hydrogen production.
Citation Information
Patent Citations
Triazinyl D-A type nitrogen-containing organic conjugated porous polymer photocatalytic material as well as preparation and application thereof
CN111804338A
Method for using metal-organic framework material to purify water, exchange ions with water or magnetize water
CN102249363A
Diyne conjugated microporous polymer and preparation method and application thereof
CN113150249A
Tri (4-acetylene phenyl) amine conjugated microporous polymer as well as preparation method and application thereof
CN114573796A
Microporous Polymers, Methods for the Preparation Thereof, and Uses Thereof
US20100240781A1
Cited By
Method for synthesizing conjugated microporous polymer through metal-free catalysis and application
CN120988254A